DETERMINATION OF THE EFFECTIVE TAX RATE (ETR) - Rizkyana, Fitrarena Widhi (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
The objective of this paper is to empirically investigate the effect of growth rate, tangible assets, audit quality, chief financial officer (CFO) expertise, political connections, and company foreign operations on the effective tax rate (ETR) of manufacturing companies in Indonesia. With 171 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2018-2021, the authors use the multiple linear regression method to identify the critical drivers of ETR. Using the purposive sampling method, 81 samples of companies with 258 units of analysis. The results confirm that ETR is significantly explained by the growth rate, tangible assets, audit quality, chief financial officer (CFO) expertise, political connections, and company foreign operations. In the case of manufacturing companies, growth rate, audit quality, and political connections are significantly driving ETR negatively, while chief financial officer (CFO) expertise and company foreign operations are significantly driving ETR positively. However, tangible assets are not significant drivers of ETR. The implications of this study show that political connections and company growth can achieve low ETR levels.